Late Embryogenesis Abundant (LEA)5 Regulates Translation in Mitochondria and Chloroplasts to Enhance Growth and Stress Tolerance - Karpinska, Barbara; Razak, Nurhayati; Shaw, Daniel S.; Plumb, William; Van De Slijke, Eveline; Stephens, Jennifer; De Jaeger, Geert; Murcha, Monika W.; Foyer, Christine H. (Frontiers in Plant Science, 2022)
Late embryogenesis abundant (LEA) proteins fulfil many roles in plants that remain poorly characterized and understood. We therefore explored the functions of the Arabidopsis LEA5 protein that is only expressed in illuminated leaves when plants are exposed to stress. Localization assays demonstrate that LEA5 is predominantly localized in the mitochondria. However, tandem affinity purification analysis revealed that LEA5 interacts with chloroplast proteins, particularly the DEAD-box ATP-dependent RNA helicase 22 (RH22). Split YFP analysis confirmed the interaction between RH22 and LEA5. While changes in the abundance of LEA5 in mutants and transgenic plants had no effect on RNA processing in chloroplasts, the abundance of translated protein products was decreased in transgenic plants constitutively expressing LEA5 (OEX 2-5) and increased in lea5 knockout mutants. In contrast, the abundance of translated mitochondrial protein products and mitochondrial electron transport rates were increased in OEX 2-5 plants and decreased in lea5 mutants. While barley lines transformed with Arabidopsis LEA5showed increased seed yields relative to controls, drought-induced inhibition of photosynthesis was greater in the transformed lines than in the wildtype. We conclude that LEA5 functions in the regulation of organellar translation, to decrease photosynthesis in plants exposed to stress.